Literature Review Role Of Matrix Metalloproteinase In Cancer Pain - Ekawaty Suryani Mastari; Fitri Aidani Ulfa; Ningrum Wahyuni; Noradina Noradina; Meriani HS (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2023)
Cancer pain occurs in more than half of cancer patients and affects their quality of life. The complexities of proinflammatory molecules in the tumor microenvironment contribute to pain. The MMPs, as proteolytic enzymes involved in cancer cell migration towards the surrounding environment, demonstrate their connection to the development of pain in cancer. As complex molecules, MMPs can be influenced by various cytokines and chemokines, mainly throughout neuroinflammation, which decreases neuron sensitivity and boosts hyperexcitability in pain-controlling mechanisms.